SINTESIS SENYAWA S-BENZOIL-MAG3 UNTUK PEMBUATAN KOMPLEK 99mTC-MAG3 - Ratnawati Kukuh (Jurnal Kimia Terapan Indonesia, 1999)
SYNTHESIS OF S-BENZOLY-MAG3 FOR THE PREPARATION OF 99mTc-MAC3 COMPLEX. 99mTc-MAG3 is a new radiopharmaceutical having similar biological properties to 131Ilabeled. Hippuran and is expected to be useful as an ideal agent for renal funtion evaluation. In order to develop the abovepreparation, it is necessary to synthesize S-benzoly-MA3 ligan. In the present study the synthesis was carried out in a 3 stepsreaction of succinimiidyl-S-benzoylthinglycolic acid from S-benzoyltingioglycolic acid, N-hydroxysuccinimide and N,N' -dicyclohexylcarbodiimide. The last step is syntesis of benzoyl-MAG3 from siccinimidyl-S-benzoylthioglycolate and glycylglycylglycine. The product has a crystaline from, colorless needles with a melting point of 203-204°C Purity testing by HPLC yielded a single peak, indicating a sufficiently pure compound. IR spectrophotometry provides proof that the compound is S-benzoyl-MAG3.